A tale of two pities: Autologous melanoma vaccines on the brink - Berd, David (Landes Bioscience, 2012)
This paper reviews and compares two autologous vaccine technologies for human melanoma that failed to obtain marketing approval after 10–15 y of clinical development—the HSP vaccine invented by Srivastava and developed by the company, Antigenics, and the hapten-modified cellular vaccine invented by Berd and developed by AVAX Technologies. Both vaccines had a strong basic science background with a well-understood mechanism of action. The HSP vaccine failed in a phase III pivotal trial, while the haptenized cellular vaccine was never adequately tested in a phase III trial because of regulatory and financial problems. It is proposed that the phase I-II clinical trials of the HSP vaccine neglected to define optimal dose, schedule, and route of administration, which, together with safety, are the major reasons for doing such trials. Therefore, the phase III trial was bound to fail because it was based on insufficient immunopharmacological information. Developers of the haptenized cellular vaccine underestimated the manufacturing and regulatory hurdles inherent to that technology and were therefore unable to complete a pivotal trial. Valuable lessons can be learned by acknowledging the mistakes made in these attempts to bring forward new treatments that could have eased the burdens of melanoma patients.